2021
DOI: 10.1002/pne2.12045
|View full text |Cite
|
Sign up to set email alerts
|

How nurses use reassurance to support the management of acute and chronic pain in children and young people: An exploratory, interpretative qualitative study

Abstract: Reassurance in the context of pediatric pain is regarded to promote distress. Typically, spoken reassurance is reported as short, generic statements (“it's ok,” “don't worry”); little research has considered wider reassuring behaviors and actions undertaken by nurses. Most studies focus on unidirectional, dyadic relationships between reassurance and pain (parent‐to‐child, professional‐to‐child) failing to capture the inherent complexities. Adopting an exploratory, interpretative, and qualitative approach, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The current study further revealed the impact of positive reassurance on nurse-patient relationships and the need to avoid giving false hopes. This finding is consistent with findings from another study that showed that nurses used language, gestures, education, and relationship-building to reassure patients [ 39 ]. Another study also revealed the need for nurses to remain calm when their patients are angry [ 40 ].…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…The current study further revealed the impact of positive reassurance on nurse-patient relationships and the need to avoid giving false hopes. This finding is consistent with findings from another study that showed that nurses used language, gestures, education, and relationship-building to reassure patients [ 39 ]. Another study also revealed the need for nurses to remain calm when their patients are angry [ 40 ].…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…Such different, albeit overlapping, agendas can result in parents/caregivers not receiving answers to questions they may find difficult to frame and clinicians missing opportunities to provide information about issues they do not appreciate are of concern to parents/caregivers. As seen in other studies, clinicians may offer reassurance to parents that does not meet their needs and lacks meaning [ 79 ]. The review highlighted that many parents/caregivers may benefit from psychological support to help them manage fears and the impact of these fears (threat).…”
Section: Discussionmentioning
confidence: 99%
“…The discussion of the findings of the review within the three affect systems of the CFT model [ 57 , 58 ] has the potential to help HCPs/clinicians understand, acknowledge and actively address and validate the fears and concerns of parents/caregivers of children with epilepsy and could help frame clinical consultations to address parental/caregiving fears and concerns. The provision of appropriate information, knowledge, meaningful clinical reassurance [ 79 ] and peer support may contribute to parents experiencing a greater sense of security (soothe) about managing daily life and the challenges of caring for their child with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…This paper reports on analyses of nurses’ responses to pediatric pain vignettes and questions about their confidence which formed Phase 1 of a mixed‐methods study to explore nurses’ “pain talk” with regard to managing children's pain. Findings from Phase 2 (qualitative interviews with a smaller sample of nurses) focus on the role of reassurance in “pain talk” 16 …”
Section: Introductionmentioning
confidence: 99%
“…Findings from Phase 2 (qualitative interviews with a smaller sample of nurses) focus on the role of reassurance in “pain talk”. 16 …”
Section: Introductionmentioning
confidence: 99%